1976
DOI: 10.1002/1097-4679(197601)32:1<189::aid-jclp2270320146>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Perception of self and significant others by alcoholics and nonalcoholics

Abstract: Ratings of self and 15 significant others on four personality factors by 47 alcoholic and 90 nonalcoholic males were analyzed by means of step-wise regression analysis and multivariate analysis of covariance. Alcoholics rated themselves less positively on extraversion and self-assertiveness (lower mean on extraversion and higher on self-assertiveness) and also judged intimate others (father, mother, and spouse) less positively on unhappiness, extraversion, and productive persistence (higher mean on unhappiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although these studies did not explicitly examine the characteristics of the self-related beliefs underlying low self-esteem, the findings are consistent with having either few positive and/or many negative beliefs about the self. A second group of studies focused on the number of positive and negative selfdescriptive adjective endorsements and found that persons with alcohol dependence endorsed fewer positive and more negative adjectives as self-descriptive compared to controls (Connor, 1962;Quereshi & Soat, 1976;Tarquinio et al, 2001;Vanderpool, 1969). Although it is not clear from the older studies that the number of positive and negative adjectives endorsed reflects the amount of positive and negative content or beliefs about the self that compose the self-concept, the Tarquinio et al (2001) study also used informationprocessing indicators that function outside of awareness to operationalize the proportion of positive to negative content included in the self-concept in persons entering treatment for alcohol dependence.…”
Section: Low Positivity and High Negativity In The Self-conceptmentioning
confidence: 99%
“…Although these studies did not explicitly examine the characteristics of the self-related beliefs underlying low self-esteem, the findings are consistent with having either few positive and/or many negative beliefs about the self. A second group of studies focused on the number of positive and negative selfdescriptive adjective endorsements and found that persons with alcohol dependence endorsed fewer positive and more negative adjectives as self-descriptive compared to controls (Connor, 1962;Quereshi & Soat, 1976;Tarquinio et al, 2001;Vanderpool, 1969). Although it is not clear from the older studies that the number of positive and negative adjectives endorsed reflects the amount of positive and negative content or beliefs about the self that compose the self-concept, the Tarquinio et al (2001) study also used informationprocessing indicators that function outside of awareness to operationalize the proportion of positive to negative content included in the self-concept in persons entering treatment for alcohol dependence.…”
Section: Low Positivity and High Negativity In The Self-conceptmentioning
confidence: 99%
“…Disturbances in the underlying structure of the selfconcept may be an important modifiable risk factor through which other more distal risk factors exert their influence. Self-concept disturbances have been implicated in the alcoholism clinical literature for decades (Connor, 1962;Drozd & Dalenberg, 1994;Matto, Miller, & Spera, 2005;Quereshi & Soat, 1976;Tarquinio, Fischer, Gauchet, & Perarnaud, 2001;White, 2000), but methodologic problems limit the usefulness of these findings. Because studies have not been based on a theoretical model of the selfconcept (Tarquinio et al is an exception), the properties of the self-concept that are linked with alcohol dependence remain unclear.…”
mentioning
confidence: 99%